Global burden of ischemic heart disease attributable to dietary factors: insights from the global burden of disease study 2021 - Wang, Yan; Yan, Daliang; Xu, Wanzi; Min, Bo; Fan, Zhiwei; Su, Hong; Zhao, Xue; Wang, Dongjin; Zhu, Yi (Frontiers in Nutrition, 2025)
BackgroundDietary risk factors remain a leading modifiable contributor to ischemic heart disease (IHD), yet global trends and inequities in diet-attributable IHD burden remain incompletely quantified. This study examines the global, regional, and demographic burden of IHD attributable to dietary risks from 1990 to 2021, and projects future trends through 2050 using data from the Global Burden of Disease (GBD) 2021 study.MethodsGBD 2021 estimates were used to quantify IHD-related deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) attributable to dietary risks across 204 countries and territories. Inequality was assessed using the slope index of inequality (SII) and concentration index (CI). A decomposition analysis evaluated the relative contributions of population growth, aging, and epidemiologic transitions to changes in burden. Future projections were modeled using autoregressive integrated moving average (ARIMA) and exponential smoothing (ES) techniques.ResultsIn 2021, IHD attributable to dietary risk factors accounted for 3,906,345 deaths, 89,929,809 DALYs, 1,851,908 YLDs, and 88,077,900 YLLs globally. The highest burden was observed in middle socio-demographic index (SDI) regions. The disease burden was markedly higher in males, with deaths and DALYs peaking at ages 60–64 and 65–69 years. Decomposition analysis revealed that population growth drove a 456.03% increase in global deaths, while accelerated aging in high SDI regions disproportionately contributed to YLDs (−161.51%). Declines in inequality indices suggested reductions in mortality, DALYs, YLDs, and YLLs disparities. Forecasts indicated a continued decline in age-standardized mortality rate (ASMR), age-standardized DALYs rate (ASDR), age-standardized YLDs rate (ASYR), and age-standardized YLLs rate.ConclusionPersistent disparities in diet-related IHD burden are shaped by sociodemographic and sex-specific dynamics. Urgent dietary interventions are needed in low- and lower-middle SDI regions, while high-SDI countries must prioritize disability prevention in aging populations. Stratified, context-specific strategies and strengthened monitoring of health inequalities are essential to reduce global cardiovascular disparities.